What do we talk about when we talk about extractivism?. Issue 3 (4th March 2021) - Szeman, Imre; Wenzel, Jennifer
ABSTRACT: The term 'extractivism' has quickly become the name for every process and practice through which value is generated for capitalism. Given this conceptual ubiquity, what analytic function does this term actually serve? This Afterword to a special issue on Extractivism reflects upon possible reasons why scholars in the humanities have recently become interested in resource extraction, among which is the desire for one's scholarly work to respond to a gathering sense of planetary environmental crisis. Such engaged scholarship may, however, be premised on faulty assumptions about the realms of discourse and experience where it can have effects. Extending Stuart Hall's insights about the need for both commitment and circumspection regarding the work our research can do in the world, this essay considers the relationship between resource extraction as a moment and process under capitalism (or socialism), and extractivism as an ideology and cultural logic that permeates social imaginaries as well as literary and other discourse. Keeping an eye on the materiality of relations and processes dubbed "extractive" is one way of avoiding the conceptual creep, metaphorical inflation, synonymical restatement, and loss of analytical precision that is now developing in the use of the term 'extractivism.'